PENGEMBANGAN MODUL BAHASA ARAB BERBASIS TEORI PSIKOLOGI PERKEMBANGAN REMAJA ELIZABETH B. HURLOCK KELAS X MA (Universitas Negeri Semarang, 2018)
The development of adolescents led to several changes, including in terms of thinking and how to learn. Adjustmentof teaching materials to students' progress will help them understand the material presented. This research designusing research and development research design (R & D). The results of this study are: 1) the number of studentswho stated that the subjects of Arabic is a difficult subject is 87.3% or a number of 42 students and 95.7% or anumber of 45 students stated that the need for development of textbooks tailored to the development the psychologyof the students of grade X Madrasah Aliyah. SWOT analysis of textbooks that have been used are books durusullughotil arabiyah and Student Worksheet